Adelocephalidae, Saturniidae, Mimallonidae, Lasiocampidae, Eupterotidae et Lymantriidae da região Sueste do Rio Grande do Sul - Biezanko, Ceslau M. (Revista do Centro de Ciências Rurais, 2008)
Na região Sueste do Rio Grande do Sul, Brasil, foram coletadas 16 espé-cies de Adelocephalidae, 36 de Saturniidae, 10 de Mimallonidae, 33 de Lasiocam-pidae, 16 de Eupterotidae, 8 de Lymantriidae e uma de Incertae Sedis. Quando conhecidos são descritos os hábitos das larvas e adultos; as plan-tas hospedeiras e épocas de ocorrência são referidas. Abstract Sixteen species of Adelocephalidae, 36 of Saturniidae, 10 ofMimallonidae, 33 of Lasiocampidae, 16 of Eupterotidae, 8 of Lymantriidae and one of Incertae Sedis were collected at Southeastern Region of Rio Grande do Sul, Brazil. Habits of adults and larvae were described when know; host plants and data of collect were refered.